Conventional treatment versus vacuum therapy for diabetic foot ulcers treatment - Potula, Vigna Sai (International Surgery Journal, 2017)
Background: This study compares the efficacy of vacuum therapy against conventional iodine povidone dressing with respect to area and time of ulcer. Methods: This study is a randomized controlled trail which was conducted in Meenakshi Medical College hospital and research institute Enathur Kanchipuram. The number of patients selected were 50, which were divided into 2 groups, Group A which consisted of 25 and received vacuum therapy, Group B which consisted of 25 and received povidone-iodine solution. Results: This study was a 16 days study, mean area of ulcer on day 0 was 11.25 cm2 in group B, 10.89 cm2 in group A. On day 6, mean area of ulcer was 10.44 cm2 in group B, 8.98 cm2 in group A. Mean area of ulcer was 10.39 cm2 in group B, 7.66 cm2 in group A on the end of the day 16. The results show that both the groups showed decrease in the area of ulcers, but patients in group A who underwent vacuum therapy have shown greater decrease in the mean area of ulcer. The decrease in surface area of ulcer was statistically significant i.e. p=0.025. There was a greater decrease in infection in group A on 16th day compared to group A on 16th day. On day 0, 48% and 60% growth of microorganisms was observed in patients of group B and group A respectively (p=0.428). On day 16, 28% and 8% growth of microorganisms was observed in patients of group B and group A respectively (p=0.034). Conclusions: Vacuum therapy was more effective compared to conventional method of povidone-iodone solution dressing in rate of healing and time of healing.